2016
DOI: 10.1136/bjophthalmol-2015-308261
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of eyelid basal cell carcinoma in England: 2000–2010

Abstract: The findings provide the current frequency and distribution of eyelid BCCs in England, highlighting opportunities for health education and improving reporting and registration of events, and for informing service planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 24 publications
(20 reference statements)
4
43
0
2
Order By: Relevance
“…However, it is interesting to draw a parallel with a recent study of basal cell carcinoma (BCC) incidence in England,13 which found that men were at increased risk aged over 50 but women were at increased risk in the 0–49 age group.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is interesting to draw a parallel with a recent study of basal cell carcinoma (BCC) incidence in England,13 which found that men were at increased risk aged over 50 but women were at increased risk in the 0–49 age group.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, BCC is the most common malignant eyelid tumor in the world [1, 40], with a male predilection [41]. However, it has been reported that eyelid BCC is more common in young females (< 50 years) [39].…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the relative risk of eyelid SCC in men compared with women was 1.9. In a similar study over 11 years (2000–2010), Saleh et al [8] found that unlike SCC, no major change in the age-standardized incidence of BCC was observed during the period between 2000 and 2010 in England. Overall, the age-standardized incidence of BCCs during the period between 2008 and 2010 was similar for males and females (4.51 per 100,000 and 4.53 per 100,000, respectively).…”
mentioning
confidence: 93%